2017
DOI: 10.1590/1519-6984.00615
|View full text |Cite
|
Sign up to set email alerts
|

Intra-specific pelage color variation in a South American small rodent species

Abstract: Intra-specific color variation is often underestimated by researchers, and among mammals, intra-specific differences in coloration are poorly documented for most species. The main goal of this study was to apply an objective color measurement methodology to the study of a specific problem: the detection, if any, of patterns of changes in the fur color of specimens of Akodon budini in relation to biological (i.e., sex) and environmental (i.e., season) variables. We hypothesize that coat color will be more homog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…This difference could be associated with a greater cellular metabolism in males, which raises the amount of CO 2 in blood (Kaneko et al, 2008;Ardiaca et al, 2013); in this sense, Freitas et al (2010) suggest that the energy metabolism of insectivorous bats may be affected by sex. Moreover, other studies have showed or suggested that sex can influence many factors related to a species (Terrien et al, 2011;Friedrich et al, 2013;Sandoval Salinas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This difference could be associated with a greater cellular metabolism in males, which raises the amount of CO 2 in blood (Kaneko et al, 2008;Ardiaca et al, 2013); in this sense, Freitas et al (2010) suggest that the energy metabolism of insectivorous bats may be affected by sex. Moreover, other studies have showed or suggested that sex can influence many factors related to a species (Terrien et al, 2011;Friedrich et al, 2013;Sandoval Salinas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…By the contrary, N. latebricola in the Cordillera Oriental occurs in the ecotonal zone between the páramo and forest whose typical vegetation is the wiry bunch grass to 1 m high and other larger species frequent of wooded environments (Voss 2003). The intraspecific color variation in rodents has been associated with the sex, age, seasonality, and habitat (e. g., Camargo et al 2016;Ríos and Álvarez-Castañeda 2012;Sandoval et al 2016). In this regard, the coloration pattern in N. latebricola seems linked with the soil and vegetation color and the exposure to be detected by predators.…”
Section: Discussionmentioning
confidence: 99%
“…We studied the same Akodon budini series previously studied for other purposes [ 25 , 26 ]. For analyses we used skins from 54 adult specimens (Additional file 1 ).…”
Section: Main Textmentioning
confidence: 99%
“…As we did in our previous studies [ 25 , 26 ] we measured color data (Additional file 2 ) through a Photo Research PR715 spectroradiometer and the SpectraWin 2 software, and inside a diffuse illumination cabin. This instrument measures the sample spectral reflectance.…”
Section: Main Textmentioning
confidence: 99%